Dynamic modeling, simulation and experimental investigation on cryogenic tank pressurization system. (3rd July 2020) - Manimaran, A; Hiremath, Somashekhar S
ABSTRACT: Propellant tank pressurization system in a cryogenic rocket engine is critical for successful mission performance. The current paper focused on dynamic analysis of the pressurization system with pneumatic pressure regulators as the significant dynamic elements. To evaluate the system dynamic behavior, a nonlinear model has been developed based on the fundamental equations by considering the compressible flow in the fluid lines and various forces inside the regulator such as pressure force, spring force, bellow force and Coulomb friction force. The simulation is carried out for nominal operating conditions of the pressure regulators and the pressurization system using AMESim simulation tool. Experimental tests have been carried out for the same parameters to validate the simulation model using a prototype assembly which is close to the system and developed in-house. The simulation results and experimental test results are found to be in good agreement. The effect of damping orifice size in the regulators and the varying tank ullage volume are studied and the obtained results are presented in the paper. The developed model serves as an ultimate a valid tool for understanding the system behavior under different operating conditions of mass flow rate, ullage volume, temperature and system operation sequence. Abbreviations: EDM: electro discharge machining; OHPR: oxygen high pressure regulator; OLPR: oxygen low pressure regulator; CMM: coordinate measuring machine; OPHPR: outlet pressure of oxygen high pressure regulator; OPLPR: outlet pressure of oxygen low pressure regulator; IPGBSPS: inlet pressure of gas bottle storage pressure system; GHe: gaseous helium; AMESim: advanced modeling environment for performing simulations; FSO: full scale output; POV: pneumatically operated valve; EP: electro pneumatic; MATLAB: matrix laboratory; AISI: American iron and steel institute